2022
DOI: 10.1093/humrep/deac066
|View full text |Cite
|
Sign up to set email alerts
|

The higher the score, the better the clinical outcome: retrospective evaluation of automatic embryo grading as a support tool for embryo selection in IVF laboratories

Abstract: STUDY QUESTION Is the automatic embryo grading function of specific time-lapse systems clinically useful as a decision support tool for IVF laboratories? SUMMARY ANSWER Blastocyst grading according to the automatic scoring system is directly associated with the likelihood of implantation and live birth, at least in treatments without preimplantation genetic testing for aneuploidy (PGT-A). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 53 publications
0
7
0
1
Order By: Relevance
“…Further evidence of the clinical efficiency of automated embryo scoring in achieving higher live birth rates has been recently disclosed. The KIDScore D5™ algorithm was shown to correlate with higher live birth rates compared to conventional morphology assessment; thus, it was proposed to function as a valuable, supportive prediction tool with the final decision being made by the assisted reproduction expert [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence of the clinical efficiency of automated embryo scoring in achieving higher live birth rates has been recently disclosed. The KIDScore D5™ algorithm was shown to correlate with higher live birth rates compared to conventional morphology assessment; thus, it was proposed to function as a valuable, supportive prediction tool with the final decision being made by the assisted reproduction expert [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence of the clinical e ciency of automated embryo scoring in achieving higher live birth rates has been recently disclosed. The KIDScore D5™ algorithm was shown to correlate with higher live birth rates compared to conventional morphology assessment; thus, it was proposed to function as a valuable, supportive prediction tool with the nal decision being made by the assisted reproduction expert [34].…”
Section: Discussionmentioning
confidence: 99%
“…In laboratories, morphological evaluation has been the main strategy applied to choose the embryos to transfer. Most reports demonstrate that the implantation, clinical pregnancy and live birth rates in the day-5 blastocyst group are significantly higher than those in the day-6 blastocyst group[ 12 , 26 , 34 ] and that morphologic parameters (degree of expansion, ICM grade, and TE grade) are significantly positively correlated with the outcomes after blastocyst transfer[ 27 , 29 ]. Some studies suggested that the transfer of euploid blastocysts tested by PGT-A can lead to higher rates of clinical pregnancy, live birth, and implantation than those of non-PGT-A tested blastocysts [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%